Botanical survey and leishmanicidal activity of grown-love (Research, Society and Development, 2020)
Grown-love (Portulaca pilosa L) is used in Amazon medicine for the treatment of diseases caused by bacteria, wound care. The objective of this work was to conduct a botanical survey of P. pilosa, as well as to evaluate its leishmanicidal activity. For the botanical studies techniques of epidermal decoupling and histological sections were used (by hand and microtome). The ethanol extract (EE) of aerial parts of P. pilosa was obtained by maceration, followed by concentration in evaporator route. The EE was fractionated by chromatographic column. The EE and fractions were analyzed in thin layer chromatography (TLC) and NMR. The leishmanicidal activity was evaluated against promastigotes and amastigotes of Leishmania amazonensis, and promastigotes of L. chagasi, with prior cytotoxicity assessment in murine macrophages. In anatomical terms, P. pilosa presents leaf surface with adaxial epidermal cells and sinuous walls. In the phytochemical prospection of the extract, terpenes and phenols were detected, among others. The analysis of the NMR suggested the presence of terpenes. All samples were inactive against promastigotes and amastigotes of L. (L) amazonensis. The dichloromethane fraction was active against promastigotes of L. (L) chagasi. The EE, dichloromethane, ethyl acetate and methanol fractions showed no cytotoxicity to murine peritoneal macrophages (CC50> 500 mg/mL). The dichloromethane fraction was promising for Leishmania, so futher studies may lead to the isolation of the active metabolite.